A SYSTEMATIC APPROACH IN STUDYING FOLKLORE BOOKS FOR STRENGTHENING LITERATURE IN ELEMENTARY SCHOOLS - Cahyati, Dwy Putri; Dina; Nurain, Fitriyanti; Nurhaliza, Siti; Buato, Irma; Mooduto, Irna (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2025)
Literary learning in elementary school plays an important role in shaping character, improving literacy, and instilling cultural values. Folklore that is rich in moral messages and close to students' daily lives is still not optimally utilized. This study uses a literature study method with a descriptive qualitative approach to examine the effectiveness of a systematic approach in learning folklore. The results of the study show that the application of systematic stages from text selection to creative activities can improve literary understanding, critical thinking, and instill character values such as honesty, responsibility, and courage. This approach is in line with the objectives of the Independent Curriculum and is relevant to be widely applied in primary schools